2014
DOI: 10.2166/hydro.2014.140
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing estimation of actual evapotranspiration and crop coefficients for a multiple land use arid landscape of southern Iran with limited available data

Abstract: The Gareh Bygone Plain is an arid area, south of Zagros Mountains, in Southern Iran, where a floodwater spreading project has been implemented for artificial recharge of groundwater. Knowledge/mapping of actual evapotranspiration for the mainland uses (natural pasture, irrigated crops and tree plantations) is of major importance for water management in this remote area. The Surface Energy Balance System (SEBS) model was used to estimate actual evapotranspiration (ET) using non-cloudy images for 32 dates of Lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…To evaluate the METRIC and SEBS models for local applications, measurements were obtained from Pakparvar et al (2014). The data included the volume of irrigation water used in farmlands as measured for two cropping seasons from December 2009 to December 2010.…”
Section: In Situ Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the METRIC and SEBS models for local applications, measurements were obtained from Pakparvar et al (2014). The data included the volume of irrigation water used in farmlands as measured for two cropping seasons from December 2009 to December 2010.…”
Section: In Situ Measurementsmentioning
confidence: 99%
“…The data included the volume of irrigation water used in farmlands as measured for two cropping seasons from December 2009 to December 2010. Guided by the recommendations from Pakparvar et al (2014), the amount of effective rainfall (recorded rainfall 3 0.7) in the volume base was added to the calculated applied water. The study reported that 24% of total input water (irrigation 1 precipitation) returns to the hydrological cycle as return flow.…”
Section: In Situ Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single K c act four stage curves were defined for remote-sensed grazed grasslands [29,30]. By contrast, other authors preferred replacing the typical four stages curve by average monthly K c act values [31].…”
Section: Introductionmentioning
confidence: 99%
“…Such models allow to directly integrating the effects related with soil water deficit or water vapor pressure in the crop ET estimation [7]. Crop coefficients can be further derived considering the ETo [8][9][10]. However, these models present greater complexity and larger amount of input data than the Kc-ETo approach [7].…”
Section: Introductionmentioning
confidence: 99%